CoNi@SiO2@TiO2 and CoNi@Air@TiO2 Microspheres with Strong Wideband Microwave Absorption. Issue 3 (20th November 2015) - Liu, Qinghe; Cao, Qi; Bi, Han; Liang, Chongyun; Yuan, Kaiping; She, Wen; Yang, Yongji; Che, Renchao
Abstract : The synthesis of CoNi@SiO2 @TiO2 core–shell and CoNi@Air@TiO2 yolk–shell microspheres is reported for the first time. Owing to the magnetic–dielectric synergistic effect, the obtained CoNi@SiO2 @TiO2 microspheres exhibit outstanding microwave absorption performance with a maximum reflection loss of −58.2 dB and wide bandwidth of 8.1 GHz (8.0–16.1 GHz, < −10 dB).